2012
DOI: 10.1016/j.cellimm.2012.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Early skin immunological disturbance after Plasmodium-infected mosquito bites

Abstract: a b s t r a c tAlthough the role of regulatory T cells (Tregs) during malaria infection has been studied extensively, such studies have focused exclusively on the role of Treg during the blood stage of infection; little is known about the detailed mechanisms of Tregs and sporozoite deposition in the dermis by mosquito bites. In this paper we show that sporozoites introduced into the skin by mosquito bites increase the mobility of skin Tregs and dendritic cells (DCs). We also show differences in MHC class II an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 28 publications
2
15
0
Order By: Relevance
“…This is supported by recent observations of induction of Treg migration in the skin of naive mice within 5-20 min following intradermal infection with malaria sporozoites (34). Hapten exposure has been shown to induce activation of an innate inflammatory response via pathways including release of danger-associated molecular patterns and pattern recognition receptor activation (28).…”
Section: Discussionsupporting
confidence: 55%
“…This is supported by recent observations of induction of Treg migration in the skin of naive mice within 5-20 min following intradermal infection with malaria sporozoites (34). Hapten exposure has been shown to induce activation of an innate inflammatory response via pathways including release of danger-associated molecular patterns and pattern recognition receptor activation (28).…”
Section: Discussionsupporting
confidence: 55%
“…Normal skin has a particularly high proportion of regulatory T cells (Tregs) in the steady state (28) and a meta-analysis of malaria vaccine studies suggested that Plasmodium -specific Tregs are induced during the skin stage of infection, potentially mediating immune tolerance to sporozoites as well as to the subsequent blood-stage of infection (30). Consistent with these results are experiments in mice that show that skin Tregs and DCs are mobilized within 30 minutes of sporozoite inoculation and that DCs downregulate MHC II and CD86 suggesting a tolerogenic response (31). The immunoregulatory environment of the skin may be reinforced by chronic immune activation or immune dysregulation due to repeated exposures to sporozoites and liver stage antigens (32).…”
Section: Human Immunity and Malariasupporting
confidence: 54%
“…The saliva also increases the levels of immunosuppressive IL-10 in the dLN, which could contribute to downregulation of Ag (OVA)-specific T cell priming in an IL-10-dependent manner (68). Another study reported that 30 min after injection by mosquitoes, P. berghei sporozoites increased the motility of regulatory T cells and decreased expression of MHC class II and CD86 in CD11c + cells in the skin of mice, corroborating the notion that regulatory T cells might suppress activation of APCs in the skin and dLN (69).…”
Section: Discussionmentioning
confidence: 67%